2014
DOI: 10.1111/1756-185x.12393
|View full text |Cite
|
Sign up to set email alerts
|

Th-17 related regulatory network in the pathogenesis of Arab patients with systemic lupus erythematosus and lupus nephritis

Abstract: Our study is the first to investigate a panel of 84 genes related to Th17 regulatory pathway in Arab SLE subjects and the first to explore the effect of current immunosuppression regimens on Th17 regulatory pathway. It paves the way for understanding the etiology of SLE and autoimmune diseases in general.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Th17 cells are now defined as a separate CD4+ T-cell subset distinct from the Th1 and Th2 cells, driving inflammatory responses in several T-cell driven autoimmune diseases [ 24 26 ]. More recently, multiple lines of evidence have indicated that Th17 cells are involved in lung cancer [ 27 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Th17 cells are now defined as a separate CD4+ T-cell subset distinct from the Th1 and Th2 cells, driving inflammatory responses in several T-cell driven autoimmune diseases [ 24 26 ]. More recently, multiple lines of evidence have indicated that Th17 cells are involved in lung cancer [ 27 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…50 Results revealed 14 genes ( IL-17A , IL-17C , IL-17D , IL-17F , IL-12RB2 , IL-23R , IL-18 , RORC , STAT4 , TRAF6 , MMP3 , CCL2 , CCL20 , and CXCL5 ) that were differentially expressed in SLE and LN patients when compared to healthy individuals. 50 The study also revealed an elevated levels of serum IL-17A and IL-17F in LN patients when compared to SLE patients. 50 In the second study, a genome-wide differential expression analysis of Arab female SLE and LN patients revealed seven candidate genes in SLE and 36 in LN, whose role in the pathogenesis of SLE and LN need to be investigated further.…”
Section: Genetic Studies Of Sle/ln In the Gcc Regionmentioning
confidence: 97%
“…5052 In the first study, a panel of 84 genes involved in the Th17-related regulatory network was investigated and the expression levels of serum interleukin (IL)-17A and IL-17F were explored in SLE and LN Arab patients. 50 Results revealed 14 genes ( IL-17A , IL-17C , IL-17D , IL-17F , IL-12RB2 , IL-23R , IL-18 , RORC , STAT4 , TRAF6 , MMP3 , CCL2 , CCL20 , and CXCL5 ) that were differentially expressed in SLE and LN patients when compared to healthy individuals. 50 The study also revealed an elevated levels of serum IL-17A and IL-17F in LN patients when compared to SLE patients.…”
Section: Genetic Studies Of Sle/ln In the Gcc Regionmentioning
confidence: 99%
“…Studies of CCL20 in the blood of SLE patients are limited and conflicting. Pan et al 56 found no difference in CCL20 mRNA in circulating leukocytes between SLE patients and HCs, whereas AlFadhli et al 69 found a marked reduction in CCL20 in whole blood of SLE patients. This reduction seen in AlFadhli et al's study may be the result of treatment the patients received or the fact that there may be a degree of dilution in the starting cDNA with plasma and other nonleukocytes.…”
Section: B Cellsmentioning
confidence: 97%
“…Pan et al 56 . found no difference in CCL20 mRNA in circulating leukocytes between SLE patients and HCs, whereas AlFadhli et al 69 . found a marked reduction in CCL20 in whole blood of SLE patients.…”
Section: Introductionmentioning
confidence: 98%